Desain Signage Informatif dan Estetis Untuk Fakultas Ilmu Komputer Universitas Almuslim di Desa Matang Glumpang Dua Kabupaten Bireuen - Hajrina, Marisa; Zuraihan; Idayani (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
The Community Service Team (PKM) has held a community service activity with the theme “Informative and Aesthetic Signage Design for the Faculty of Computer Science, Almuslim University in Matangglumpangdua Village, Bireuen Regency.” This community service activity aims to provide clear information through informative and aesthetically pleasing signage design for the community or users visiting the Faculty of Computer Science at Almuslim University. The activity was carried out in three stages: preparation, implementation, and reporting. The results achieved from this community service are (1) an understanding of the concept of signage design that is appropriate or characteristic of the Faculty of Computer Science and Almuslim University, (2) the application of engineering knowledge in designing or drawing signage that can provide information about the location of the Faculty of Computer Science at the university (3) the creation of a design that applies the concept of a computer circuit board as a visual identity for the Faculty of Computer Science and the concept of Islamic Relief as a geometric pattern to strengthen the image of Almuslim University. This community service activity was carried out as an effort to provide an informative yet aesthetic design concept so that visitors can immediately recognize the presence of the Faculty of Computer Science. The result is a signage design for the Faculty of Computer Science that is able to provide information related to its identity and the beauty of its form.